Addressing a volatile subject: adaptive measurement of Australian digital capacities. Issue 7 (6th June 2020) - Magee, Liam; Kearney, Emma; Bellerose, Delphine; Collin, Philippa; Crabtree, Louise; Humphry, Justine; James, Paul; Notley, Tanya; Sharma, Anjali; Third, Amanda; Yorke, Samantha
ABSTRACT: Measuring the dynamic shape of digital practices and their near-ubiquitous relationship to daily life is an elusive quest, one that must contend with temporal and relational limits. Research instruments employing categories and indicators struggle with the transient and interconnected character of the digital 'social fact'. Longitudinal studies pose special difficulties: a 1990s study of browsing and searching would need to be updated to account for the rise of blogging, gaming and media sharing in the 2000s, and again for mobile devices, virtual reality and home automation in the 2010s. Accounting for the volatility of digital life requires, we argue, an adaptive theoretical approach that acknowledges its integral temporal and relational character. We introduce 'digital capacity' as the key organising concept for this approach. Alongside the productive capacities of digital objects, the concept doubles as a description of the responsive and generative abilities of digital users. Such capacities are not invariant, and evolve reflexively through multiple sociotechnical milieu: local neighbourhoods, regional configurations of law and infrastructure, and global networks, standards and platforms. Today, capacities respond, for example, to complex arrangements of face-to-face relations, nation-state norms, and the increasing prevalence of mobile devices, telecommunications and platforms. Despite the rapidity and complexity of this change, practitioner and research communities need some stability in definitions and measures of capacities, and we further discuss an approach, based on community indicator work, to research instrument design that admits both comparison and sensitivity to time, place and context. We include illustrative data from a pilot study of Australian digital capacities.